Sediments distribution of trace metals in a coastal lagoon (Southern Sardinia, Mediterranean Sea): assessment of contamination and ecological risk. Issue 8 (14th September 2018) - Atzori, Giulia; Aru, Violetta; Cesare Marincola, Flaminia; Chiarantini, Laura; Medas, Daniela; Sarais, Giorgia; Cabiddu, Serenella
ABSTRACT: Coastal lagoons are subject to several sources of contaminations. To shade light on the contamination level of the Santa Gilla lagoon (Tyrrhenian Sea) we investigated the spatial distribution of Cr, Ni, Pb, Zn and Hg in sediments and their correlation with grain size and organic matter contents. Moreover, sediment contamination levels and the ecological risk associated with metal concentration were assessed using different abiotic indicators. The lagoon is characterised by low levels of contamination, with exceptions for Pb and Hg, whose distribution reflects the position of an old chlor-alkali plant and that of an airport. These results indicate that the restoration put in place 30 years ago have not reached the expected target and that the presence of the airport deserves further attention. In the outer section of the lagoon, where clam fishery occurs, we observed low levels of contamination suggesting that such artisanal fishery could somehow help mobilising metals. We conclude that the area exposed to Hg pollution, though tentatively restored, still suffers of a potential risk of ecosystem deterioration. We pinpoint that further investigations on the mobility, bioavailability and toxicity of metals are needed to finally address the actual impairment of the Santa Gilla lagoon.